Dampak Sosial Kehadiran Trans Jogja terhadap Mobilitas Masyarakat Perkotaan di DIY - Febri Puja Rahayu; Dwi Afrika Puspita Ningrum; Aman (Sawala : Jurnal Administrasi Negara, 2026)
This study examines the technological innovation of Trans Jogja as a public transportation system that adapts to the dynamics of the Industrial Revolution 4.0 in the Special Region of Yogyakarta. The problem addressed in this research is the limited understanding of how digital transformation—such as electronic ticketing, GPS-based fleet monitoring, real-time information services, and smart mobility integration—contributes to improving the efficiency, accessibility, and sustainability of urban transportation. Using a qualitative descriptive method supported by document analysis, observations, and interviews, this study analyzes the operational system and technological features implemented in Trans Jogja. The findings show that technological innovation has enhanced service reliability, reduced transaction barriers, strengthened passenger data management, and supported environmentally sustainable mobility. However, challenges remain, including uneven digital literacy, infrastructure limitations, and inconsistent real-time accuracy. The study concludes that Trans Jogja represents a strategic model of technology-based public transportation capable of supporting smart city development and promoting sustainable urban mobility in Yogyakarta.